Tabah Black Rice Mutant Performance as the results of Cobalt-60 Gamma 200 Gray Radiation in the Tidal Rice Field - ., Osini; Rianto, Fadjar; ., Darussalam (Jurnal Sains Mahasiswa Pertanian, 2020)
The aim of this study to get information on the performanceof morphological and agronomic characteristics of black rice mutant Tabah. Tabah black rice have been irradiated with Co-60 200 Gray . The study was carried out on theBalai Benih Induk, Sungai Kakap Kabupaten, Kubu Raya, from November 2017 -May 2018. The black rice seedling planted ontidal rice field.Observed performance of plant held on the sample, were 40 sample plants. Eachhole be planted by 1 seedling.Planting distane was 25 x 25 cm.The results of the study shows that the average height of seedlings was 33.31 cm. The average of leaf length is 45.58 cm, leaf widthwas 1.62 cm. Medium and hairy leaf surface, erect leaf angle shape, medium flag leaf angle, flat and drooping, light green leaf neck color, white leaf ear color, dark green leaf color, and stout black rice leaf midrib, green. The average length of the leaf ligulaewas 2.34 cm, white and the shape of the ligulae leaves 2-cleft. The number of tillers that appeared on average were 11.58 tillers, Â the ability to breed, which was little to moderate. The average plant height was 119.45 cm, the shape of the stem is erect, the color of the item was yellow, and the stiffness of the stem was strong. The panicle emerge of the whole panicle comes out, and the neck was moderate, has an average length of 26.67 cm. compact and medium panicle type, panicle shaft droops. The color of the grain tip has a brown criterion, the average seed length is 9.9 mm / 1 cm. The average seed width is 2.92 mm. The average seed thickness is 1.92 mm. the weight fertilized grain of 100 seeds 2.6g. Average plant age 151.Keywords: Agronomic Characteristics, Black Rice, Mutant, Radiation, Mophological Characteristi